Aceh: Pusat Dakwah Islamiyah pada Abad ke 16 dan ke 18 - Haji Baba, Sidik (Jurnal Usuluddin, 1995)
The article describes the arrival of Islam in Aceh and the development of Islamic administration in the area. It also discusses the expansion of Islamic education.